Diseño de una herramienta computacional para la selección de un sistema de conectividad integrando las nuevas tecnologías para la producción y seguridad operacional durante el completamiento de pozos de Ecopetrol S.A. (2018)
Decision making is highly important for profitability in a hydrocarbon production project. Currently, the constant change in the industry makes engineers and managers require high skill and expertise for databases analysis looking for the promotion and execution of the best options in benefit of their companies. Undoubtedly, one of the operations of greater relevance to obtain the best economic revenue in a hydrocarbon well, is connectivity generation with reservoir either perforating or stimulating it. It is determinant to know the completion record in a field to select the most appropriate and suitable system in case you want to develop a perforating process in a new or existing well. Likewise, it is necessary to include new technologies and connectivity systems, due to these have multiple technical optimizations that guarantees to be efficient in non-productive times reduction and operational efficiency.